Inter-rater reliability and validity of the Australian Football League´ kicking and handball tests - Cripps, A. J.; Hopper, L. S.; Joyce, C. (Journal of Sports Science & Medicine, 2015)
Talent identification tests used at the Australian Football League`s National Draft Combine assess the capacities of ath-letes to compete at a professional level. Tests created for the National Draft Combine are also commonly used for talent identification and athlete development in development path-ways. The skills tests created by the Australian Football League required players to either handball (striking the ball with the hand) or kick to a series of 6 randomly generated targets. Asses-sors subjectively rate each skill execution giving a 0-5 score for each disposal. This study aimed to investigate the inter-rater reliability and validity of the skills tests at an adolescent sub-elite level. Male Australian footballers were recruited from sub-elite adolescent teams (n = 121, age = 15.7 ± 0.3 years, height = 1.77 ± 0.07 m, mass = 69.17 ± 8.08 kg). The coaches (n = 7) of each team were also recruited. Inter-rater reliability was as-sessed using Inter-class correlations (ICC) and Limits of Agreement statistics. Both the kicking (ICC = 0.96, p < .01) and handball tests (ICC = 0.89, p < .01) demonstrated strong relia-bility and acceptable levels of absolute agreement. Content validity was determined by examining the test scores sensitivity to laterality and distance. Concurrent validity was assessed by comparing coaches` perceptions of skill to actual test outcomes. Multivariate analysis of variance (MANOVA) examined the main effect of laterality, with scores on the dominant hand (p = .04) and foot (p < .01) significantly higher compared to the non-dominant side. Follow-up univariate analysis reported signifi-cant differences at every distance in the kicking test. A poor correlation was found between coaches` perceptions of skill and testing outcomes. The results of this study demonstrate both skill tests demonstrate acceptable inter-rater reliable. Partial content validity was confirmed for the kicking test, however further research is required to confirm validity of the handball test.